Technologies Of Students' Learning Motivation Formation - Abduvaliyeva Nilufar Nematullayevna (Academia One Publishing, 2024)
In this article, the role of technology in the formation of educational motivation of schoolchildren, some issues related to inability to properly direct educational motivation as the main factor causing difficulties in mastering subjects are included.
Keywords: social motive; educational motive; motivation